Carotenóides totais em Pothomorphe umbellata (L.) Miq. cultivadas in vitro - Yepez, C. C B [UNESP]; Lima, G. P P [UNESP]; Padilha, P. M. [UNESP]; Corrêa, L. C. [UNESP]; Tejada, E. S. (My University, 2008)
The aim of the present work was to compare the content of carotenoids between callus and regenerated plants of Pothomorphe umbellate. Germinated seeds (40 days old) were inoculated in different concentrations and combinations of BAP (benzylaminopurine) and NAA (naphthalene acetic acid) in order to stimulate the callus' production. After 60 days of culture, the callus containing some shoots were transferred to organogenesis medium (GA 3 0.1 mg L -1, BAP 0.5 mg L -1) for 40 days. Next, they were subcultivated in a medium for seedling growth (without regulators) for 40 days. Callus (collected after 60 days) and seedlings (collected after 140 days) were frozen in liquid nitrogen and kept under -80°C for future carotenoids' analysis. The highest concentration of carotenoids was found in plants cultivated in medium without regulators. The callus did not showed difference concerning the culture medium; however, they presented lower content of carotenoids in relation to plants.
Total carotenoids in Pothomorphe umbellata (L.) Miq. cultivated in vitro
Keywords: Callus; Growth regulators; Medicinal plants; Seedlings; arylacetic acid derivative; carotenoid; liquid nitrogen; phytohormone; callus culture; freezing; higher plant; in vitro study; nonhuman; organogenesis; plant seed; Pothomorphe umbellata; seedling; Lepianthes peltata; Pothomorphe